Short-term outcomes of subtotal colectomy for splenic flexure tumors: a single-center experience - Mehmet Aslan; Oktay Karakose (Medicine Science, 2023)
Splenic flexure tumors are a subtype of colon tumors whose treatment is still debated. We aim to evaluate the surgical methods and short-term outcomes of splenic flexure tumors. Fourteen patients with colonic tumors at or near the splenic flexure who underwent subtotal colectomy in the surgical oncology department of Samsun Training and Research Hospital between August 2017 and March 2020 were retrospectively evaluated in terms of postoperative morbidity, mortality, and early oncologic outcomes. Of the fourteen patients evaluated, twelve were urgent and two were elective. Four patients underwent additional organ resection as a curative surgery. The pathology was colonic adenocarcinoma in all patients, and the histotype was mucinous in five patients (35.7%). Lymph node positivity was detected in six patients (42.8%) and metastasis in one patient (7.1%). Postoperatively, two patients (14.2%) developed surgical site infection, and one patient (7.1%) died. Eight (57.1%) patients complained of more frequent defecation, with a mean bowel movement frequency of 3±1.6 times daily. Based on our clinical experience, subtotal colectomy is appropriate for emergency surgical treatment of splenic flexure tumors, whereas left hemicolectomy is appropriate under elective conditions. [Med-Science 2023; 12(3.000): 737-40]